PENGARUH HASIL BELAJAR PEMASARAN ONLINE DAN HASIL BELAJAR KEWIRAUSAHAAN TERHADAP KINERJA PENJUALAN ONLINE PESERTA DIDIK SMK NEGERI SURABAYA - Effendi, Hari (UNIVERSITAS NEGERI SURABAYA, 2017)
This study aimed to analyze whether there is influence learning outcomes online marketing on the performance of online sales, to analyze whether there is influence learning outcomes of entrepreneurship on the performance of online sales and analyze whether there is influence learning outcomes online marketing and entrepreneurship simultaneously on the performance of online sales is applied to learners class 10 SMK Field of expertise Business Management, Marketing Package expertise in Surabaya. The research was conducted in the second semester of 2014 - 2015 with this quantitative approach, the students SMK Surabaya, namely SMK 10, SMK Negeri 4 and SMK Negeri 1 Surabaya with a sample of 135 learners. Based on the results of data analysis, it can be concluded that there is a significant influence on the results of online marketing learning online sales performance, there is a significant effect on the performance of entrepreneurial learning outcomes online sales, there is a significant effect simultaneously learning outcomes online marketing and entrepreneurship learning outcomes for online sales performance.